Long-term follow-Uu and treatment of postoperative permanent hypoparathyroidism in patients with medullary thyroid carcinoma: differences in complete and partial disease - Leidig-Bruckner, Gudrun; Bruckner, Thomas; Raue, F.; Frank-Raue, K. (Hormone and metabolic research, 2016)
This study aimed to identify factors influencing long-term outcome in complete or partial postoperative hypoparathyroidism (parathyroid hormone ≤10 or >10 ng/l, respectively) in medullary thyroid carcinoma (MTC). It was designed as retrospective, long-term follow-up with single-center outpatient visits. Quality of treatment, renal calcification, and function were evaluated. In 33 patients with MTC and postoperative hypoparathyroidism, current medication includes: calcium (73%), calcitriol (73%), alfacalcidol (6%), dihydrotachysterol (3%), and cholecalciferol supplements (21%). Mean hypoparathyroidism duration was 15.9±9.4 years. Initially, 15% of patients received high cholecalciferol dosages. Initial calcium dosages were higher (1 542±1 179 mg/day) than final dosages (1 188 ± 595 mg/day) (p<0.05); calcitriol dosages remained constant. Over the median observation period of about 12 years it was found that serum calcium was within the target range (2.0-2.3 mmol/l) in 63% of visits, decreased (<2.0 mmol/l) in 20.4%, high-normal (2.4-2.6 mmol/l) in 15.8%, and increased (>2.65 mmol/l) in 0.9% of visits. Calcitriol dosages were 0.73±0.22 μg/day and 0.47±0.20 μg/day in patients with complete (n=13) and partial (n=20) hypoparathyroidism, respectively (p=0.008). Renal function decreased slightly during follow-up (eGFR: 102±22 vs. 90±27 ml/min). eGFR was negatively correlated with hypoparathyroidism duration (r=−0.35, p=0.05). Of 9 patients with renal calcification, 5 had received high initial cholecalciferol doses. eGFR was lower in patients with than in those without calcification (77±17 vs. 95±29 ml/min) (p=0.07). At least one tetanic episode occurred in 60.6% of patients, and 9% had repeated tetanic complaints. In conclusion, severity of hypoparathyroidism affects treatment: Partial hypoparathyroidism required lower calcitriol dosages than complete hypoparathyroidism. Renal calcifications occurred more frequently in patients treated initially with high cholecalciferol dosages. Impaired renal function was related to hypoparathyroidism duration and renal calcification.